2013
DOI: 10.1007/s40135-013-0011-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Dry Eye

Abstract: The tear film is a complex mixture of molecules such as lipids, mucins and water, whose function is to protect the eye from external factors such as environmental stimuli, traumas and infections. It is secreted by specific structures, but also, in part, derives from the blood stream. Substances taken with food can directly or indirectly influence tear film composition so inducing changes of the ocular surface. When the tear film is altered a condition known as dry eye may develop. Diet derived substances can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Decreased pyridoxal 5'-phosphate plasma level decreased B6 vitamin synthesis due to pyridoxal synthesis (Girard, Matte, 1999). It has been reported that vitamin B6 deficiency affects the ocular surface and causes dry eyes (Aragona et al, 2013). Our study has shown that dry eye and visual blurring side effects occur with alteration of thiamine metabolism.…”
Section: Discussionsupporting
confidence: 61%
“…Decreased pyridoxal 5'-phosphate plasma level decreased B6 vitamin synthesis due to pyridoxal synthesis (Girard, Matte, 1999). It has been reported that vitamin B6 deficiency affects the ocular surface and causes dry eyes (Aragona et al, 2013). Our study has shown that dry eye and visual blurring side effects occur with alteration of thiamine metabolism.…”
Section: Discussionsupporting
confidence: 61%
“…The inter-individual variability in each group, however, was high, with coefficients of variation exceeding 30%. This was not entirely surprising as there are genetic and environmental factors that can individually affect tear production and composition, such as hormonal and nutritional stimuli [ 15 , 16 ]. In these experiments, the saline wash group contained little or no protein, indicating that collection by microcapillary tube efficiently removes the protein content from the tear film.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a differential diagnosis should include CF in cases of corneal disorders in children without prior CF NBS. Nonsevere corneal abnormalities, such as keratinization, can be reversible after supplementation, especially with vitamin A and nutritional compensation [ 97 ]. Corneal ulcers require the implementation of intensive topical treatment with fluoroquinolones and often systemic empiric antibiotic therapy, while, after revealing the pathogenic factor in culture, targeted antibiotic therapy should be implemented; however, in severe cases—not amenable to pharmacological treatment—corneal keratoplasty is necessary [ 98 ].…”
Section: Management Of Cf-related Ocular Complicationsmentioning
confidence: 99%